Shifting the Focus : Intra-acting with Diverse Agencies and Happy Objects in a Day Center of Disability Services - Jaakonaho, Liisa (Aalto-yliopisto, 2024)
The article is based on the author’s experiences of facilitating creative movement groups in a disability services day center. Through artistic and performative research, she investigates different forms of agency in and around the movement groups. She draws on theoretical perspectives from critical disability studies, feminist new materialism and affect studies, particularly focusing on Sara Ahmed’s (2010) notion of the “happy object,” to challenge the human-centric view of arts education and artistic agency. She proposes a shift of focus in arts education from individual agents to the intra-action of diverse agencies in art making, teaching, and learning in diverse contexts.
Keywords: taiteellinen tutkimus; taidekasvatus; vammaiset; taiteellinen työ; taidepedagogiikka; kokemukset